EDUKASI TENTANG TERAPI KOMPLEMENTER DALAM KEHAMILAN DI WILAYAH KERJA PUSKESMAS BAJENG DI KABUPATEN GOWA: EDUKASI TENTANG TERAPI KOMPLEMENTER DALAM KEHAMILAN DI WILAYAH KERJA PUSKESMAS BAJENG DI KABUPATEN GOWA - Nelly Nugrawati; Nur Ekawati; Ayu Wijaya; Andi Muhammad Adam Aminudddin (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2023)
Complementary therapy in health services is a non-conventional treatment aimed at improving the health status of the community. These therapies include promotive, preventive, curative, and rehabilitative efforts, although currently existing complementary therapies are one of the options during pregnancy to reduce common complaints or discomfort. The purpose of this Community Service activity is to provide knowledge to mothers about complementary therapies in pregnancy. This activity was carried out on September 28, 2023 at Puskesmas Bajeng, Gowa Regency with a total of 15 pregnant women who were carried out by providing information about the definition, purpose and benefits as well as types of complementary therapies for pregnancy. The results of the service activities showed that the pre-test results of mothers with good knowledge were only 2 people (13.33%) and post-test good knowledge of 14 people (93.33%). Through health education about complementary therapy in pregnancy, it is hoped that there will be an increase in the knowledge and attitude of pregnant women in utilizing complementary therapy so that it can be beneficial and safe for the mother and fetus.